The new world of human resources and employment : how artificial intelligence and process redesign is driving dramatic change - Miller, Tony (Management consultant) (Human resource management and organizational behavior collection., 2019)
Artificial Intelligence (AI) will change the world as we know it within only a few years. Its most significant impact will be on our Human Resource (HR). What is AI and what's made it significant are contained in this concise book. The book has a wide readership and will provide for many organizations the catalyst for swift change to take strategic advantage of what AI has to offer. In this book are some of the HR processes that can be changed today, suggestions on what's available, and some resources you may wish to use. The evidence so far is that many HR functions have not developed AI strategies, in a false belief that AI is in the future. But it's here and it's happening, and the change is expediential in its growth; we are in the change window for a massive paradigm shift, now is the time for immediate action. The arrival of cognitive deep learning in AI will herald a massive paradigm shift in employment. The change is happening now. At the forefront of the change will be the human resource. This book is the catalyst for change many HR functions will need. Advice on progress with AI and specifically HR processes that will be most directly affected are contained within this concise book. This is truly a golden opportunity for human resource professionals, organizational designers, business managers, business students, and workforce planners. Organizations that act, and act fast, will be the beneficiaries of the AI revolution.